Contribution of Aberrant Toll Like Receptor Signaling to the Pathogenesis of Myelodysplastic Syndromes - Paracatu, Luana Chiquetto; Schuettpelz, Laura G. (Frontiers in Immunology, 2020)
Toll like receptors (TLRs) are a family of pattern recognition receptors that play a central role in the innate immune response. These receptors are expressed on a wide variety of immune and non-immune cells, and they help shape the immune response to infection and injury through the recognition of pathogen-associated molecular patterns (PAMPs) as well as endogenous damage-associated molecular patterns (DAMPs). Accumulating evidence suggests that, in addition to regulating mature effector immune cells, TLRs can influence the immune response from the level of the hematopoietic stem cell (HSC). HSCs express TLRs, and exposure to TLR ligands influences the cycling, differentiation and function of HSCs, with chronic TLR stimulation leading to impairment of normal HSC repopulating activity. Moreover, enhanced TLR expression and signaling is associated with myelodysplastic syndromes (MDS), a heterogenous group of HSC disorders characterized by ineffective hematopoiesis and a high risk of transformation to acute leukemias. In this review, we will discuss the role of TLR signaling in the pathogenesis of MDS, focusing on the known direct and indirect effects of this type of signaling on HSCs, the mechanisms of TLR signaling upregulation in MDS, the changes in TLR expression with disease progression, and the therapeutic implications for modulating TLR signaling in the treatment of MDS.